Optimasi pembuatan garam Ulva lactuca menggunakan response surface methodology: Optimization production process of Ulva lactuca salt using response surface methodology - Khairunnisa, Anis; Cesrany, Mahaldika; Farida, Iftachul; Astiana, Ika; Utari, Siluh Putu Sri Dia; Niken Prawesti; Lailatussifa, RR Radipta; Kurniawati, Made Devi; Kusuma, Ni Kadek Sita Anyaniti; Murtiningsih, Ni Made Ayu Meylia (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Ulva lactuca seaweed is a potential raw material for the production of functional salts. The obstacle faced was the low yield. The purpose of this study was to determine the optimum process conditions for the production of U. lactuca salt based on the highest yield percentage, chemical quality, and sensory properties using the Response Surface Methodology method with the Box-Behnken (BBD) design. The method of making seaweed salt uses three variables with three levels, namely, the ratio of U. lactuca flour addition and aqueous solvent (A = 1:5, 1:10, 1:15), extraction time (B = 10, 15, and 30 min), and extraction temperature (C = 40, 55, and 70℃). A combination of these three factors resulted in a total of 15 experiments. The equation model was tested using analysis of variance (ANOVA) with α = 0.05. The optimized U. lactuca salt was tested for its chemical quality, heavy metal contamination, and sensory characteristics. The results showed that the optimal treatment for producing the highest seaweed salt yield was flour and solvent ratio of 1:13.5, extraction time of 12 min, and extraction temperature of 70℃. This treatment produced a yield response of 31.81±1.63%, which was a difference of 0.82% compared to the predicted response of 31.55%. The resulting U. lactuca salt had an ash content of 59.97%, protein 3.6%, fat 0.25%, carbohydrate 15.46%, moisture 10.49%, NaCl content 27.31%, iodine